Acceleration of Green Transitions on the Base of Port Organizational Ecosystem’s Resilience Enhancement: A Socio-Technological Approach - Elena Valioniene; Erika Zuperkiene; Birute Placiene (Applied Sciences)
Seaports are pivotal nodes in global trade, under increasing pressure to expedite green transitions while navigating the complexities of modern economic and environmental challenges. This research investigates the intricate relationship between the resilience of port organizational ecosystems and the successful implementation of green transitions. Employing a combination of focus group interviews and participatory observation, the study explores the primary obstacles, particularly the insufficiency of managerial capacity, which hampers the integration of technological innovations. Challenges identified include outdated infrastructure, cybersecurity vulnerabilities, and the imperative for sustained investment in new technologies, along with the need to promote a culture of sustainability. Experts highlight the crucial role of managerial competencies and continuous learning in overcoming these barriers. Furthermore, the research underscores the importance of fostering strong partnerships among stakeholders, including government bodies, industry associations, and environmental organizations. The findings offer valuable insights for policymakers, port managers, and other stakeholders seeking to navigate the challenges for ensuring a sustainable future for the maritime sport organizational ecosystems and maritime industry.